The Influence of Salary and Allowances on Employee Productivity at GraPARI Telkomsel Manokwari Regency - Pakadang, Damayanti Veronika; Karubaba, Kaleb Yohan; Balia, Nikolina (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
This study aims to analyze the influence of salary and allowances on employee productivity at GraPARI Telkomsel in Manokwari Regency. The research method used is a quantitative approach with multiple linear regression techniques. Data were obtained through questionnaires distributed to 45 employees and analyzed using validity tests, reliability tests, and classical assumption tests before conducting multiple linear regression analysis. The results show that salary and allowances have a significant simultaneous and partial effect on employee productivity. Salary has a regression coefficient of 0.541 with a significance value of 0.007, while allowances have a regression coefficient of 0.489 with a significance value of 0.011. Both variables together increase employee productivity, with the F-test showing a significance value of 0.000. The implication of this study is the importance of company policies in providing competitive salaries and adequate allowances to enhance employee productivity.